The Dynamics of Students’ Independence and Basic Psychological Needs: A Comparative Study of General Boarding Schools and Islamic Boarding Schools - Ranni Rahmayanthi; Syarifuddin Dahlan; Diah Utaminingsih; Ratna Widiastuti (Department of Guidance and Counseling, FIP, Undiksha, 2026)
The achievement of independence is a crucial developmental task during adolescence; however, boarding school environments often create a dilemma between collective disciplinary control and students’ need for individual autonomy. Imbalances in the fulfillment of basic psychological needs at school may lead to low initiative, maladaptive behavior, and disciplinary violations due to weak self-regulation. This study aimed to analyze differences in the level of independence and fulfillment of basic psychological needs between students in general boarding schools and Islamic boarding schools. The study employed a comparative descriptive quantitative approach involving 175 students as research participants, consisting of 90 students from general boarding schools and 85 students from Islamic boarding schools. Data were collected using the Adolescent Independence Scale and the validated Basic Psychological Needs Scale. Data analysis was conducted using the Independent Sample t-test. The results revealed significant differences in the level of independence (p = 0.002) and basic psychological needs (p = 0.000), in which students from general boarding schools showed higher scores than students from Islamic boarding schools. These findings indicate that environments providing greater autonomy support are more effective in facilitating students’ independence. In conclusion, institutional parenting patterns that balance social regulation with opportunities for personal choice serve as an important foundation for psychological well-being. The implications of this study highlight the need for Self-Determination Theory based guidance and counseling services focused on strengthening decision-making skills in boarding school environments.